Non-parametric approaches to whole farm planning the case of Uraya Farms, Inc. in Butuan, Agusan del Norte, Philippines - Abad, Trixia Mona T.; Sarmiento, Jon Marx P.
Majority of the individual farms in Mindanao rely on the production of the minor tropical fruits such as durian, lanzones, rambutan, watermelon, pummelo, and mangosteen among others in generating income. In contrast with the major fruits like banana and mango, the minor tropical fruit industry has not thrived due to decreasing farm land area, increasing prices of inputs, fluctuating prices of produce, and poor management practices of fruit farms. These issues underlie several implications in the farm-level. Thus the study sought to know to know the different issues of an agribusiness entrepreneur regarding the management of a fruit farm. This study focused on assessing the whole-farm plan of Uraya Farms, Inc. in Butuan specifically, its durian, lanzones, and mangosteen enterprises. The methods Non-preemptive Linear Goal Programming was used to assess the goals of the farm and determine if the farm operates at an optimal level, Cost-Data Envelopment Analysis (cost-DEA) to determine any inefficiency on the product of fruits, and Total Factor Productivity to determine if the enterprises experience growth in terms of productivity, after which model farms and priority enterprises were identified. Though farm was able to achieve all of its goals simultaneously, there were inefficiencies observed. The sources of technical and cost inefficiency of the farm were excessive labor days and the over utilization of fertilizers ammophos, soluphos, compost, an potash. With total factor productivity, a regress in growth was observed within the three years considered. The model farm areas identified were the areas efficient in production and had positive productivity growth and the priority enterprises were the enterprises which serve as the main income generating enterprises of each farm area.
Thesis, Undergraduate (B.S. Agribusiness Economics)-U.P. Mindanao